1994
DOI: 10.1116/1.578990
|View full text |Cite
|
Sign up to set email alerts
|

Microloading effect in reactive ion etching

Abstract: The etch rate of silicon, during reactive ion etching (RIE), depends on the total exposed area. This is called the loading effect. However, local variations in the pattern density will, in a similar way, cause local variations in the etch rate. This effect is caused by a local depletion of reactive species and is called the microloading effect. Silicon wafers patterned with silicon dioxide have been etched in order to study the microloading effect. The pattern consists of a large exposed area and narrow lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 0 publications
0
55
1
Order By: Relevance
“…It was reported that, for the larger patterned area, the distance from the center to the edge is larger, which may poses difficulty in removing the reaction byproduct from the center of array. 51 This leads to the higher etching rate at the edge of the array than that at the center. Figure 2(b) shows the timelapse images of microneedles array in the etching process.…”
Section: A Sem Images Of a Silicon Microneedles Arraymentioning
confidence: 99%
“…It was reported that, for the larger patterned area, the distance from the center to the edge is larger, which may poses difficulty in removing the reaction byproduct from the center of array. 51 This leads to the higher etching rate at the edge of the array than that at the center. Figure 2(b) shows the timelapse images of microneedles array in the etching process.…”
Section: A Sem Images Of a Silicon Microneedles Arraymentioning
confidence: 99%
“…Unlike the TEM analysis reported above, in the AFM measurements the roughness of the silicon surface has been measured on large areas of the sample and not in the nanoscale holes: indeed, measuring roughness inside nanoscale holes is not within reach of the existing state-of-the-art AFM techniques. The AFM measurements proved inconclusive as we could not detect any difference in roughness on the large areas within the experimental error: this however does not disprove the TEM analysis conducted within the holes and is compatible with ARDE, the effect where the etch rate depends on the aspect ratio (depth/width) of the features to be etched [69].…”
Section: Discussionmentioning
confidence: 87%
“…In the case of dry etching the hole shows a deep dig in the crystalline silicon as the etching does not land selectively on the silicon substrate. The dig in silicon is reduced by decreasing the hole size due to the aspect ratio dependent etching (ARDE) phenomenon [69]. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A special case of the loading is the microloading effect. The microloading effect is the etching rate degradation due to the high density of a pattern, the main mechanism for microloading is, etchant depletion [17,18]. Etchant depletion happens inside an etching trench and it is due to the difficulty for the etchant species to be replenished, as the etching opening reducing.…”
Section: Nano-scale Etchingmentioning
confidence: 99%
“…More details are explained in the following paragraphs. The loading effect [17] is the decrease of the etching rate of the reactive ion etching due to the increased area exposed to the SF 6 plasma. In our test structures more than 90% of total wafer area is exposed.…”
Section: Nano-scale Etchingmentioning
confidence: 99%